Implikasi Upacara Masegeh di Pura Prajapati Desa Pakraman Tambakan pada Penguatan Aspek-Aspek Ekonomi Pariwisata - I Ketut Wardana Yasa (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
Human beings have three debts according to the teachings of Hinduism called tri rna and these debt must be paid in his lifetime. Man in debt of God is paid with Dewa Yajña. Humans owe to parents; ancestors are paid with Pitra Yajña. Human in debt with teachers or rsi yajna can be paid by Rsi Yajña. Humans who have debts will try to immediately pay them. Similarly, the debt owned by a person or a family either to his ancestors or to God will always be paid in accordance with their ability through yajña (a sincere sacrifice). Yajna ceremony in the form of masegeh ceremony has an impact on strengthening the aspects of the economy and aspects of tourismdevelopment in the Village Pakraman Tambakan.